Sophisticated, iconic and magical: A qualitative analysis of brand charisma. (July 2019) - Semaan, Rania W.; Ashill, Nick; Williams, Paul
Abstract: Despite the breadth of research examining charismatic leadership in the psychology and management literature, research on charisma and its relationship to brands has remained scant. This is due in part to the lack of consensus regarding what brand charisma really is. The objective of this paper is to define the conceptual domain of brand charisma and the behaviors associated with its legitimization. Specifically, we present an exploratory study to shed light on the behavioral attributes of charismatic luxury brands. The results of the study demonstrate the importance of eleven core behaviors as perceived by luxury brand consumers and support a multidimensional conceptualization of the brand charisma construct. Key implications are discussed along with suggestions for future research.